Assessment of the relationship between nutritional status, inflammatory marker CRP and serum immunoglobulin G, M, A in adults - Śmidowicz, Angelika; Reguła, Julita (Progress in Nutrition, 2018)
Background. Inflammation is the common denominator of atherosclerosis, cardiovascular diseases, obesity, metabolic syndrome and type 2 diabetes. There are studies confirming the involvement of the immune system in acute myocardial infarction, metabolic syndrome, obesity and diabetes. However, data evaluating the relationship between markers of nutritional status and the concentration of immunoglobulins are insufficient. Aim. The aim of this study was to investigate the relationship between selected markers of nutritional status, age, inflammatory markers CRP and immunoglobulin G, A and M in adults. Material and Methods. The study included 114 people aged 45+. Nutritional status was assessed on the basis of anthropometric measurements, lipid profile indicators and fasting glucose. The concentration of the inflammatory marker CRP was determined by the high-sensitivity method and the concentration of immunoglobulin G, A, M by the immunoturbidimetric method. Assessment of the gender differences was based on one-way analysis of variance and analysis of the relationship between nutritional markers, CRP and immunoglobulin based on linear regression analysis. Results. A major problem in the study population was the occurrence of metabolic disorders in the form of excess body weight, lipid profile and carbohydrate metabolism disorders. It was shown that IgA levels correlated positively with waist circumference and WHR. No significant correlations were found between the remaining nutritional status markers assessed, C-reactive protein and IgA, IgG and IgM concentrations. Conclusions. The findings confirm the hypothesis that the immune system is involved in the pathogenesis of obesity, in particular the abdominal type. More research is needed to explore mechanisms which increase serum IgA among obese patients. However, one limitation of this study is the relatively small experimental group. It is necessary to conduct tests on a large population, which could confirm these dependencies.